PENINGKATAN KREATIVITAS GURU MELALUI PELATIHAN PENGGUNAAN APLIKASI CANVA DALAM PEMBELAJARAN DI SD MUHAMMADIYAH 1 CANDI - Ramadhan, Syahrul; Hidayatullah, Ariyansyah Arief; Nurjanah, Indah; Rochmania, Ainur; Sufyanto, Sufyanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community service activities at SD Muhammadiyah 1 Candi aim to address the challenges teachers face in designing creative and engaging learning media. The program includes an introduction to the Canva application, providing teachers with opportunities to create learning media projects, as well as offering guidance and evaluation. As a result, seven teachers successfully gained new knowledge and skills in using Canva, which enhanced their creativity in designing affective and visually appealing learning media. This activity made a positive contribution to the development of teachers’ competencies and enriched students’ learning experiences.